The French Free Soil principle in the Atlantic World - Peabody, Sue (Africana Studia, 2020)
This paper will address the origins and development of the French legal maxim that a slave setting foot on metropolitan French soil became free, as well as comparisons to instantiations of this principle in the British and Portuguese empires of the late eighteenth and nineteenth centuries. Keywords: France, Slavery, Free Soil, 18th century, race